Differential Responses of the Catalytic Efficiency of Ammonia and Nitrite Oxidation to Changes in Temperature - Taylor, Anne E.; Mellbye, Brett L. (Frontiers in Microbiology, 2022)
Microbially mediated nitrification plays an important role in the nitrogen cycle, and rates of activity have been shown to change significantly with temperature. Despite this, the substrate affinity of nitrifying bacteria and archaea have not been comprehensively measured and are often assumed to be static in mathematical models of environmental systems. In this study, we measured the oxidation kinetics of ammonia (NH3)-oxidizing archaea (AOA), NH3-oxidizing bacteria (AOB), and two distinct groups of nitrite (NO2-)-oxidizing bacteria (NOB), of the genus Nitrobacter and Nitrospira, by measuring maximum rates of activity (Vmax), half-saturation constant (Km), and overall catalytic efficiency (Vmax/Km) over a range of temperatures. Changes in Vmax and Km with temperature were different between groups, with Vmax and catalytic efficiency increasing with temperature in AOA, while Vmax, Km, and catalytic efficiency increased in AOB. In Nitrobacter NOB, Vmax and Km increased, but catalytic efficiency significantly decreased with temperature. Nitrospira NOB were variable, but Vmax increased while catalytic efficiency and Km remained relatively unchanged. Michaelis-Menten and Haldane kinetic models of NH3 oxidation and NO2- oxidation based on the data collected correctly predict nitrification potential in some soil incubation experiments, but not others. Despite previous observations of coupled nitrification in many natural systems, our results demonstrate significant differences in response to temperature strategies between the different groups of nitrifiers; and indicate the need to further investigate the response of nitrifiers to environmental change.